THE IMPACT OF ENERGY ALTERNATIVES ON SOME MACROECONOMIC VARIABLES IN IRAQ: NATURAL GAS AND SOLAR ENERGY AS A MODEL (World Economics and Finance Bulletin, 2025)
The Iraqi economy faces complex challenges in the energy sector, as a result of its almost total dependence on crude oil and natural gas to generate electricity. This dependence has led to fragility in energy security, and high financial costs as a result of importing gas, as the annual import bill is estimated at about $4 billion, which is an increasing burden on the public budget and the balance of payments. In contrast, Iraq has a large and untapped potential in the field of solar energy, which is represented by high annual solar radiation rates, and provides large areas suitable for investment. This research aims to analyze the overall economic impact of the shift towards solar energy as an alternative strategic option, by reducing domestic gas consumption and directing it towards export, thus enhancing public revenues, reducing dependence on imports, and contributing to economic stability. The research also discusses the institutional and technical challenges that hinder the energy transition, and proposes practical policies to overcome them, in a way that supports diversification of sources of income and sustainable growth. The study finds that solar energy is not only an environmental solution, but also an effective macroeconomic tool that contributes to improving macroeconomic indicators, especially reducing the fiscal deficit, improving the trade balance, and increasing employment opportunities. The research calls for the adoption of a comprehensive national energy security strategy, combining economic efficiency, environmental justice and sovereign decision-making autonomy.
Keywords: For macroeconomics; solar energy; natural gas